Acute Exercise Effect on Glomerular Filtration in the Elderly - Ramos Jimenez, Arnulfo (2020)
Introduction: There is a decrease in Glomerular Filtration Rate (GFR) in older adults and the exercise practice may lead to changes in renal function. Purpose: To evaluate the effect of different intensities of acute exercise on elderly population GFR. Methods: 20 apparently healthy older adults (69,8 ± 4 years) performed 3 exercise tests a week apart: one maximal and 2 submaximal (80% and 60%). Blood samples were collected to determine serum creatinine and to estimate GFR, before and after each exercise test. Results: A significant post-exercise decline in GFR, estimated from serum creatinine values, was observed in the maximal and submaximal 80% tests (p <0,05). Conclusion: Maximum and sub-maximum acute physical exercise at 80% intensity causes a decrease in glomerular filtration in apparently healthy older adults.